Matrix stiffness regulates glucose-6-phosphate dehydrogenase expression to mediate sorafenib resistance in hepatocellular carcinoma through the ITGB1-PI3K/AKT pathway - Ruimei Ren; Shan Zhang; Zhan Peng; Xiaomeng Ji; Hao Song; Qiuxiao Wang; Xiangyin Sun; Huiyu Wang; Yinying Dong (Cell Death and Disease)
Abstract Sorafenib is an antiangiogenic and antiproliferative chemotherapeutic drug that plays a crucial role in the treatment of patients with advanced hepatocellular carcinoma (HCC). However, resistance to sorafenib greatly limits its therapeutic efficacy. This highlights the importance of determining the mechanisms underlying resistance to antiangiogenic therapy. In this study, we found that the extracellular matrix (ECM) stiffness was closely related to the prognosis of HCC patients and chemotherapy resistance. Using atomic force microscopy, we assessed ECM stiffness in tumor samples from 30 HCC patients treated with sorafenib, and the ECM stiffness in sorafenib-resistant patients was significantly greater than that in those who responded to sorafenib treatment. In a liver orthotopic xenograft model, reducing tumor ECM stiffness by inhibiting LOX enzyme activity significantly enhanced the efficacy of sorafenib and suppressed tumor progression. We found that glucose-6-phosphate dehydrogenase (G6PD) is regulated by ECM stiffness and is involved in resistance to sorafenib. Further in vitro and in vivo experiments confirmed that ECM stiffness can upregulate G6PD expression through the ITGB1-PI3K/AKT pathway, mediating sorafenib resistance in HCC. Clinical tissue microarray analysis revealed that the expression of collagen I, α-SMA, ITGB1, p-AKT, and G6PD was associated with sorafenib resistance in HCC patients. These results indicated that reducing ECM stiffness can increase the sensitivity of HCC to sorafenib and that the ITGB1-PI3K/AKT-G6PD cascades may serve as potential therapeutic targets for reversing sorafenib resistance.